The Impact of Land Requisition on Peasant Life in China. (January 2020) - Chen, An
Since the late 1990s, land requisition has given rise to peasant protests in much of rural China. The literature is mostly focused on how local governments attempted to expropriate land for various purposes—at the expense of the peasants' interests. This article goes beyond the exploitation/resistance binary and offers an in-depth analysis of the benefits and costs of land requisition to peasants through an examination of the requisition deals and peasants' post-requisition lives. It argues that the extent to which peasants benefited or suffered from land requisition was determined by multiple factors which differed region by region, village by village, and household by household. These factors include the purposes of land requisition, the commercial potential of the land, the local government's coffers and its land compensation package, the extent of the peasants' reliance on farming to earn a living, their non-farming skills, social networks, and competitiveness in labor markets.